Nutrients enrichment experiment on seawater samples at Pulau Perhentian, Terengganu - Mohamed, Khairul Nizam; Amil, Rahanim (Elsevier, 2015)
The northeast monsoon wind over about maximum of 30 knots to the east coast of Peninsular Malaysia, literally drive the vertical and upwelling activities which lift nutrient-rich water to the ocean surface water. The availability of these nutrients was essential for the phytoplankton growth and its compositions play an important role in ocean primary production, nutrient cycle and food web. Hence, the mean elemental ratio of marine organic particle 106C/16N/1P must be highly conserved, to ensure the phytoplankton productivity, associated with the availability of iron that critically depends on the speciation. To clarify the nutritional status at Pulau Perhentian, Terengganu during the post northeast monsoon, we conducted nutrients enrichment incubation experiment. The growth of phytoplankton in different combination of nutrients was observed during incubation period. Our initial data could suggest a limited condition of phytoplankton growth during pre-northeast monsoon event at study area